Research of the Effect of Profile Deviation on Contact Characteristic of Helical Gear - Luo Tao; Qin Xunpeng; Huang Jinjing (Jixie chuandong)
In order to study the influence of profile deviations on the contact characteristic of the helical gear,the involutes equation containing the profile form deviation and profile slope deviation is deduced.On the meanwhile,a finite element model containing tooth profile deviations is established.Based on this finite element model,the effect law of the profile form deviation and profile slope deviation on the maximum contact stress,bending stress and load distribution is obtained.The result suggests that the contact strength and bending strength of gears is reduced by the profile form deviation and profile slope deviation and the load distribution status is changed.When the profile form deviation is larger than 5μm or the profile slope deviation equals to ±0.5°,the gearwill gradually change tooth meshing number from three to two,then two to one,which brings certain impact on the carrying capacity of gear.